High occurrence of multidrug-resistant Esche-richia colifrom Holstein-Friesian cattle in Northern Portugal: a One Health challenge - Quinteira, S. (2023)
Escherichia coli is currently a leading pathogen for deaths associated with antimicrobial resistance (AMR). AMR related to food-producing animals is a public health risk requiring a One Health approach. Animals are major reservoirs of antibiotic resistant E. coli which can easily reach humans through the food chain, direct contact, or the environment. To analyze the AMR profiles of E. coli in fecal samples from Holstein-Friesian cattle, as information on AMR from dairy farming in Portugal is scarce. Samples (n=112) collected from 7 different farms at Northern Portugal were pooled during February-March 2023 based on age group (8 calves and 8 cows per farm). Characteristic E. coli colonies were selected from MacConkey Agar supplemented with or without antibiotics (4 µg/ml cefotaxime; 3 µg/ml colistin), for confirmation by MALDI-TOF mass spectrometry and antimicrobial susceptibility testing (AST), according to EUCAST/CLSI guidelines. ESBL phenotype were searched using the Double-Disk Synergy Test. Presumptive E. coli isolates (n=110) representing different farming production systems were obtained and 51 representatives were identified by MALDI-TOF and tested by AST. From both calves and cows, 95% and 63% of the E. coli isolates exhibited resistance to ≥1 antimicrobial classes and multidrug resistance (MDR, resistance to ≥3 antimicrobial classes), respectively. Isolates were mostly resistant to gentamycin (88%), ampicillin (72%), amoxicillin plus clavulanic acid (63%), tetracycline (63%) and cefotaxime (53%). Only two isolates showed susceptibility two all tested antibiotics. ESBL activity was observed in 21% of E. coli isolates. All analyzed pools were classified as MDR. This is one of the first studies on AMR rates of E. coli from dairy cattle in Northern Portugal. It reveals a high prevalence of MDR E. coli, which is a worrying finding and emphasize the need of a multisectoral One Health approach to minimize its impact.